Trauma Healing With Play Therapy For Student of Senior High School 16 Pandeglang Banten - Handoyo, Alfiandy Warih; Afiati, Evi; Muhibah, Siti; Hakim, Ibrahim Al (Universitas Mercu Buana Yogyakarta, 2020)
A year pass after Tsunami Banten - Lampung disaster, there were some victims who still feeling trauma. This study aims to describe about the implementation of play therapy method for reduce students survivor of the Tsunami Sunda Strait disaster trauma. This research method is descriptive, that will describe about doing play therapy for trauma healing on trauma survivor. The results of the assessment showed that there are some students experience physical, emotional, and habitual disorders. Play therapy activities carried out in three stages:Â initiation, outdoor activities, and indoor activities. The final results show that after participating in play therapy activities, students feel more comfortable and relax because they can pour out their fears. Students also begin to reduce anxiety and fear.Â